2014
DOI: 10.1007/978-3-319-07635-5_60
|View full text |Cite
|
Sign up to set email alerts
|

Public Perception and Acceptance of Electric Vehicles: Exploring Users’ Perceived Benefits and Drawbacks

Abstract: In this research, we describe an empirical study, which aimed at identifying influencing factors on acceptance of electric vehicles. Understanding individual arguments and to reach a high usage rate of these vehicles in the public and a broad acceptance, the identification of possible prousing motives as well as perceived drawbacks is essential, which would allow a sensitive and individually-tailored communication and information policy. Using an exploratory approach, a questionnaire study was carried out in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…Among the different ages, the ascribed usefulness of self‐driving cars, affordability, social support, and lifestyle fit were important determinants for acceptance. This is consistent with previous studies on mobility (Hohenberger, Spörrle, & Welpe, ; Ziefle, Beul‐Leusmann, Kasugai, & Schwalm, ), which show that user factors (e.g., age and gender) considerably impact risk perceptions and acceptance decisions.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…Among the different ages, the ascribed usefulness of self‐driving cars, affordability, social support, and lifestyle fit were important determinants for acceptance. This is consistent with previous studies on mobility (Hohenberger, Spörrle, & Welpe, ; Ziefle, Beul‐Leusmann, Kasugai, & Schwalm, ), which show that user factors (e.g., age and gender) considerably impact risk perceptions and acceptance decisions.…”
Section: Introductionsupporting
confidence: 92%
“…On top of that, cars provide social esteem, technological novelty, and branding (Sheller, , ). The recent developments toward autonomous driving partially contradict the historically formed relationship between people and their experience with cars (Kirsch, ; Ziefle, Beul‐Leusmann, Kasugai, & Schwalm, ). Further, studies on innovation culture (e.g., Birkinshaw, Hamel, & Mol, ) point out that change of familiar patterns and concepts in an innovation process leads to discomfort, independent of the type of innovation: “the introduction of something new to the state of the art creates ambiguity and uncertainty for the individuals in an organization.…”
Section: Introductionmentioning
confidence: 99%
“…The health impacts account to respiratory illnesses and premature mortality caused by particulate matter, and NOx and SOx emissions emanating from vehicle tailpipes and from power generation (for the e-jeepney), while non-health impacts account to corresponding visibility reduction, soiling, and material damage [46]. As the urban air pollution in the Philippines has considerable health implications at about 1.5% of the country's GDP [46], the shift from combustion engines to EVs is beneficial to health and environment, especially when the government also transitions to greener sources of energy [45,47,48]. On the other hand, one study [46] estimated a negative USD 1470/vehicle of GHG savings from the e-jeepney, while it was positive USD 928/vehicle for the EURO-4 diesel jeepney.…”
Section: Discussionmentioning
confidence: 99%
“…Many recent studies have found that users of electrified vehicles tend to be disproportionately male, younger, higher income/wealthier, and college educated with fewer or no children at home (Caperello and Kurani 2011;Langbroek et al 2017;Nayum et al 2016;Plötz et al 2014), although some exceptions to these general patterns emerge; for example, Ziefle et al (2014) found women and older generations to be more interested in electrified vehicles. Much of the research on these vehicles with respect to risk focuses on "range anxiety" related to the constrained range of BEVs and the relative sparseness of vehicle-charging infrastructure as compared to the gasoline refueling infrastructure used by internal combustion engine vehicles.…”
Section: Electrified Vehiclesmentioning
confidence: 99%